2015
DOI: 10.1155/2015/128256
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Elemental Composition ofMalabar spinach, Lettuce, Spinach, Hyacinth Bean, and Cauliflower Vegetables Using Proton Induced X-Ray Emission Technique at Savar Subdistrict in Bangladesh

Abstract: The concentrations of 18 different elements (K, Ca, Fe, Cl, P, Zn, S, Mn, Ti, Cr, Rb, Co, Br, Sr, Ru, Si, Ni, and Cu) were analyzed in five selected vegetables through Proton Induced X-ray Emission (PIXE) technique. The objective of this study was to provide updated information on concentrations of elements in vegetables available in the local markets at Savar subdistrict in Bangladesh. These elements were found in varying concentrations in the studied vegetables. The results also indicated that P, Cl, K, Ca, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 43 publications
0
2
1
1
Order By: Relevance
“…Another comparative study of the accumulation of calcium in different vegetables reported the following; lettuce 95213 ± 101 mgkg -1 , spinach 86606 ± 102 mgkg -1 , hyacinth bean 84615 ± 79 mgkg -1 and cauliflower 80743 ± 87 mgkg -1 These values were all higher than those reported in this study [16].…”
Section: Calciumcontrasting
confidence: 70%
“…Another comparative study of the accumulation of calcium in different vegetables reported the following; lettuce 95213 ± 101 mgkg -1 , spinach 86606 ± 102 mgkg -1 , hyacinth bean 84615 ± 79 mgkg -1 and cauliflower 80743 ± 87 mgkg -1 These values were all higher than those reported in this study [16].…”
Section: Calciumcontrasting
confidence: 70%
“…Children as young as 8 years old need 1.2 to 1.5 mg per day, whereas adult men of any age up to 70 years old need 1.9-2.3 mg per day. Females up to the age of 70 need 1.6-1.8 mg per day [68]. The quantity of manganese discovered was found greater (0.281 mg/L) in roots and lesser (0.975 mg/L) in leaves.…”
Section: Discussionmentioning
confidence: 84%
“…A Tabela 3 mostra a distribuição das concentrações dos metais (macronutrientes) nos alimentos estudados. Como pode ser observado, não há, por parte do Decreto Nº 55871, de 26 de março de 1965-ANVISA, Limite Máximo de Tolerância para esses elementos (Fahad, et al, 2015).…”
Section: Resultsunclassified